EPIDEMIOLOGY, CLINICAL ASPECTES,LABORATORY DIAGNOSIS AND TREATMENT OF RICKESIAL DISEASES IN THE MEDITERRANEAN AREA DURIN COVID-19 PANDEMIC:A REVIEW OF THE LITERATURE - Andrea De Vito; Nicholas Geremia; Maria Sabrina Mameli; Pier Andrea Serra; Vito Fiore; Gaia Giovanna Maria Rocchitta; Susanna Maria Francesca Nuvoli; Renato Lobrano; Angela Spanu; Antonio Cossu; Sergio Babudieri; Giordano Maddeddu (Mediterranean Journal of Hematology and Infectious Diseases)
The purpose of the present review is to give an update regarding the classification, the epidemiology, the clinical manifestation, the diagnoses, and the treatment of the Rickettsiae species present in the Mediterranean area.